Danazol alters mitochondria metabolism of fibrocystic breast Mcf10A cells. (October 2017) - Irgebay, Zhazira; Yeszhan, Banu; Sen, Bhaswati; Tuleukhanov, Sultan; Brooks, Ari D.; Sensenig, Richard; Orynbayeva, Zulfiya
Abstract: Fibrocystic Breast Disease (FBD) or Fibrocystic change (FC) affects about 60% of women at some time during their life. Although usually benign, it is often associated with pain and tenderness (mastalgia). The synthetic steroid danazol has been shown to be effective in reducing the pain associated with FBD, but the cellular and molecular mechanisms for its action have not been elucidated. We investigated the hypothesis that danazol acts by affecting energy metabolism. Effects of danazol on Mcf10A cells homeostasis, including mechanisms of oxidative phosphorylation, cytosolic calcium signaling and oxidative stress, were assessed by high-resolution respirometry and flow cytometry. In addition to fast physiological responses the associated genomic modulations were evaluated by Affimetrix microarray analysis. The alterations of mitochondria membrane potential and respiratory activity, downregulation of energy metabolism transcripts result in suppression of energy homeostasis and arrest of Mcf10A cells growth. The data obtained in this study impacts the recognition of direct control of mitochondria by cellular mechanisms associated with altered energy metabolism genes governing the breast tissue susceptibility and response to medication by danazol. Highlights: The mitochondria-mediated effects of danazol on fibrocystic breast cells were investigated. Fast non-genomic effects of danazol include alterations of cell oxidative phosphorylation. Long-term effects of danazol consist of modulations of energy metabolism signaling and cell growth arrest.